Keanekaragaman Gastropoda Pada Habitat Lamun Di Perairan Desa Tayando Yamtel Kecamatan Tayando Tam Kota Tual - Gea, Liyatin; Khouw, A. S.; Tupan, Ch. I. (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
The gastropod community is an important component in the food chain in seagrass beds, where the gastropods are the detritus feeder. Research on the diversity of gastropods in seagrass habitat in the waters of Tayando Yamtel Village, Tam City, Tual District, was conducted in March-May 2018, using the quadrant linear transect method. The results of measurements of environmental parameters in Tayando Yamtel waters are: an average pH of 8.55; DO 6.59 µg / l; salinity 32.36 ‰; temperature of 29 ° C; TDS 24.7 mg / l; current velocity (0.42 m / sec) is classified as low current; and a depth of 1.5 m. Gastropod research results obtained 862 individuals consisting of 15 families and 30 species of gastropods, while for seagrass obtained 3 species namely Cymodocea rotundata, Cymodocea serrulata and Thalassia hemprichii. The highest value of composition and gastropod density at Station I was dominated by Psedeovertagus aluco species at 62.73% and 3.708 (ind / m2), while at Station II were 28.01% and 0.93 (ind / m2) and Station III were 38.46% and 0.15 (ind / m2) are dominated by Strombus gibberulus species. Based on the gastropod ecological index value, the index value of species diversity and harmony is included in the medium category and the index value of dominance is in the low category. Keywords: Gastropoda, Seagrass, Tayando Yamtel